Using Recycled Coal Ash from Thermal Power Plants and Rice Husk Ash as Alternative Aggregates for the Manufacturing of Terrazzo Tiles - Nguyen Thi Minh Trang; Nguyen Thi Thanh Huong; Ngo Anh Dao Ho (Environment and Natural Resources Journal)
This study investigated the technical specifications of Terrazzo tiles manufactured using coal ash from thermal power plants and rice husk ash (RHA) to partially replace sand and cement as primary aggregates. Sample bricks with different mixed ratios of fly ash, bottom ash (slag), and RHA were produced with a hydrostatic-press machine with a standard mode of 400×400×30 mm. Our results showed that the brick density, flexural strength, and water absorption were significantly affected by the variation of fly ash and RHA content. The optimum ratio by weight of aggregate ingredients was found to be fly ash of 10%wt., RHA of 30%wt., and slag of 5%wt., accompanied by crushed stone at 55%wt. This produced brick products comparable to Terrazzo tiles, type 2, Mac 4.0. This classification satisfies the Vietnamese national standard for exterior bricks, and also is competitive with commercial quality in the local market. The reuse and recycling of waste from thermal power plants and RHA for manufacturing new construction material was thus demonstrated successfully in this study. This helps to emphasize the trend of net zero emissions, and further encourages the concept of reutilization towards sustainable development.